Human Serum Albumin Can Regulate Amyloid-β Peptide Fiber Growth in the Brain Interstitium: IMPLICATIONS FOR ALZHEIMER DISEASE - Stanyon, Helen F. (American Society for Biochemistry and Molecular Biology, 2012)
Alzheimer disease is a neurodegenerative disorder characterized by extracellular accumulation of amyloid-β peptide (Aβ) in the brain interstitium. Human serum albumin (HSA) binds 95% of Aβ in blood plasma and is thought to inhibit plaque formation in peripheral tissue. However, the role of albumin in binding Aβ in the cerebrospinal fluid has been largely overlooked. Here we investigate the effect of HSA on both Aβ(1–40) and Aβ(1–42) fibril growth. We show that at micromolar cerebrospinal fluid levels, HSA inhibits the kinetics of Aβ fibrillization, significantly increasing the lag time and decreasing the total amount of fibrils produced. Furthermore, we show that the amount of amyloid fibers generated directly correlates to the proportion of Aβ not competitively bound to albumin. Our observations suggest a significant role for HSA regulating Aβ fibril growth in the brain interstitium.